2006
DOI: 10.1124/mol.106.027946
|View full text |Cite
|
Sign up to set email alerts
|

Short Polybasic Peptide Sequences Are Potent Inhibitors of PC5/6 and PC7: Use of Positional Scanning-Synthetic Peptide Combinatorial Libraries as a Tool for the Optimization of Inhibitory Sequences

Abstract: Positional scanning-synthetic peptide combinatorial libraries (PS-SPCLs) are powerful molecular tools to identify enzyme substrate and potent inhibitory sequences and also to provide crucial information about active site determinants. PS-SPCLs have been surveyed for furin, proprotein convertase (PC)2, PC1/3, and PACE4 and proven efficient to identify potent peptidyl inhibitors in the low nanomolar range for furin and PC1/3. We report herein the screenings of nonamidated and acetylated hexapeptide PS-SPCLs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…To further corroborate this finding, we pharmacologically inhibited pPCs in all above cell lines using the cell-permeable peptide HDA, which efficiently blocks both furin and PC7 with an inhibition constant (K i ) of 106 and 1875 nM, respectively (24). In our previous studies we observed that HDA treatment specifically impaired MHC I surface expression in T2(1-2DN), but not in T2 (TAPwt) cells, consistent with a requirement for post-ER stabilization of MHC I only in the former cell line (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…To further corroborate this finding, we pharmacologically inhibited pPCs in all above cell lines using the cell-permeable peptide HDA, which efficiently blocks both furin and PC7 with an inhibition constant (K i ) of 106 and 1875 nM, respectively (24). In our previous studies we observed that HDA treatment specifically impaired MHC I surface expression in T2(1-2DN), but not in T2 (TAPwt) cells, consistent with a requirement for post-ER stabilization of MHC I only in the former cell line (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…2D) underscores the exclusive involvement of this particular pPC, whereas a practically complete furin knockdown is totally neutral in this sense. Of note, HDA has a broad inhibitory capacity against most pPCs (including PC7), blocks furin activity efficiently in vivo, and actually has a .10-fold higher potency toward furin than toward PC7 (24). Further corroborating the selective requirement for PC7, but not furin, more than half of the peptide peaks that are specifically detected in the T2(1-2DN)-and T2(1-2DN/FUR↓)-derived peptide spectra disappear from the respective spectrum of T2(1-2DN/PC7↓) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although less efficient than Furin, PC7 specifically cleaves overexpressed substrates at Arg2 residues both in vitro (22)(23)(24)(25)(26)(27)(28)(29) and in cell lines (30 -39). Northern blot analyses revealed a wide expression of PC7 mRNA in all rat tissues and cell lines analyzed (40), suggesting that it may have multiple physiological functions.…”
mentioning
confidence: 99%
“…Apart from peptides derived from endogenous inhibitors (see Section 13.4.3.1), positional scanning of synthetic peptide combinatorial libraries has been used to identify potential inhibitory peptides for PC1 [222,223] and PC2 [222] as well as PC5A [224], and to get information about active-site determinants. Accordingly, S 5 , S 4 , and S 3 subsites of PC1 appear to resemble those of PC2, while the S 6 subsite of PC1 appears to be more selective than that of PC2 [222].…”
Section: Peptide Inhibitorsmentioning
confidence: 99%